The effect of cold chamber temperature on the cadaver's electrolyte changes in vitreous humor and plasma. (February 2019) - Murthy, Abilash Srinivasa; Das, Siddhartha; Thazhath, Harichandrakumar Kottyen; Chaudhari, Vinod Ashok; Adole, Prashant Shankarrao
Abstract: Determination of time since death is one of the important objectives of a medicolegal autopsy. The level of electrolytes present in the body fluids acts as a helpful indicator in this regard. Nowadays cold chambers are present in most of the autopsy centres where the body is stored for a variable period of time at a temperature which is different from the environmental temperature. This study was undertaken to know the effect of the cold chamber temperature on the changes in sodium, potassium and chloride levels of vitreous humor and plasma and also to estimate the time since death from the levels of these electrolytes. For this, the study subjects were exposed to the cold chamber temperature (in a range of +2 °C to +4 °C) for a variable duration of time before beginning the autopsy. The results obtained substantiate the fact that the temperature of the cold chamber has a significant effect on the change in vitreous humor potassium level. In subjects exposed to the cold chamber, there was a statistically significant negative correlation between the sodium and chloride levels of vitreous humor with time since death. The R-squared value for the regression equation to predict time since death from vitreous humor sodium level was found to be 0.0916 and was considered a significant predictor of time since death. Highlights: Negative correlation between vitreous sodium level and TSD with p-value 0.002 Negative correlation between vitreous chloride level and TSD with p-value 0.009 Regression equation to predict TSD from vitreous sodium level. R-squared value was 0.0916 and a significant predictor of TSD.